2006
DOI: 10.1038/sj.eye.6702353
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in reducing power of aqueous humor originating from glaucomatous rabbits

Abstract: Aim To evaluate changes in the reducing power of aqueous humor (AH) with cyclic voltammetry (CV) and HPLC-EC. Methods NZW Rabbits exhibiting a sporadic mutation causing bilaterally buphthalmus eyes were set for intra ocular pressure (IOP) and eye size measurements. AH was obtained under anesthesia, from congenital glaucomatic rabbits (CGR, n ¼ 6) and age-matched controls (CON; n ¼ 6). The AH samples were analysed by CV and HPLC-EC. Results CGR IOP was found to be significantly higher than in CON (33.571.1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Erdurmus M et al [30] and Ferreira SM et al [31] reported that serum level of total antioxidant capacity was decreased in patients with primary open-angle glaucoma and pseudoexfoliation glaucoma. In addition, aqueous humor UA levels were significantly lower in the congenital glaucoma rabbit model compared with the age-matched controls [32]. Sorkhabi R et al [22] reported a significant correlation between a higher aqueous humor 8-hydroxydeoxyguanosin level and lower antioxidant capacity levels in the serum of patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Erdurmus M et al [30] and Ferreira SM et al [31] reported that serum level of total antioxidant capacity was decreased in patients with primary open-angle glaucoma and pseudoexfoliation glaucoma. In addition, aqueous humor UA levels were significantly lower in the congenital glaucoma rabbit model compared with the age-matched controls [32]. Sorkhabi R et al [22] reported a significant correlation between a higher aqueous humor 8-hydroxydeoxyguanosin level and lower antioxidant capacity levels in the serum of patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of a relationship between nutrition and age‐related eye diseases is not novel 2 . Elevated plasma levels of antioxidants have a protective benefit against oxidative stress, which has been implicated as the major contributor to the development of each of these ocular disorders 3–10 . Nutritional therapies involving phytochemical interventions are emerging as being potentially effective in reversing the progression of age‐related eye problems (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…45 A decrease in the aqueous humor redox state is also effected by a decrease in the aqueous humor antioxidant content in human 46 and congenital glaucoma rabbits. 8 Further research is needed to clarify what is the exact source of the MAPK proteins found in the aqueous humor, and whether the MAPK proteins are phosphorylated in the aqueous humor, suggesting that active kinases and phosphatases are present in the humor, or the kinase phosphorylation of the different MAPK proteins took place in other ocular cells, and an unknown secreting mechanism is present in relevant tissues.…”
Section: Discussionmentioning
confidence: 98%
“…7 Recently, it was shown in congenital glaucomatic rabbits that chronically elevated IOP causes a significant decrease in the levels of aqueous humor antioxidants, as evaluated by cyclic voltammetry and HPLC. 7,8 Nitric oxide (NO) is known to relax TM cells and ciliary muscle. 9 A deficit in nitric oxide synthase-like activity in the ciliary muscle and outflow pathway, leading to lowered NO production, has been found in primary open-angle glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%